Features of accounting software in Ukraine - Samokhvalova, A. Yu. (ТДАТУ, 2019)
Security - financial data is the company’s most valuable information and must be prevented from falling into the wrong hands or getting lost by mistake. Accounting and finance systems prevent accounting from being jeopardized, and keep an extra copy in case you need to retrieve them.
Keywords: Computerization accounting; business process; accounting